Senescence Is Associated With Elevated Intracellular Resting [Ca2 +] in Mice Skeletal Muscle Fibers. An in vivo Study - Mijares, Alfredo; Allen, Paul D.; Lopez, Jose R. (Frontiers in Physiology, 2021)
Aging causes skeletal muscles to become atrophied, weak, and easily fatigued. Here, we have tested the hypothesis that normal aging in skeletal muscle cells is associated with Ca2+ intracellular dyshomeostasis and oxidative stress. Intracellular Ca2+ concentration ([Ca2+]i), resting intracellular Na+ concentration ([Na+]i) and reactive oxygen species (ROS) production were measured in vivo (superficial gastrocnemius fibers) using double-barreled ion-selective microelectrodes, and in vitro [isolated single flexor digitorum brevis fibers] using fluorescent ROS sensor CM-H2DCFDA in young (3 months of age), middle-aged (12 months of age), and aged (24 months of age) mice. We found an age-related increase in [Ca2+]i from 121 ± 4 nM in young muscle cells which rose to 255 ± 36 nM in middle-aged and to 409 ± 25 nM in aged cells. [Na+]i also showed an age-dependent elevation, increasing from 8 ± 0.5 mM in young muscle fibers, to 12 ± 1 mM in middle-aged and to 17 ± 1 mM in old muscle fibers. Using the fluorescent ROS sensor CM-H2DCFDA we found that these increases in intracellular cation concentrations were associated with significantly increased basal ROS production as demonstrated by age related increases in the rate of dichlorodihydrofluorescein fluorescence. To determine is this could be modified by reducing ROS and/or blocking sarcolemmal Ca2+ influx we administered flufenamic acid (FFA), a non-steroidal anti-inflammatory drug which is also a non-selective blocker of the transient receptor potential canonical channels (TRPCs), for 4 weeks to determine if this would have a beneficial effect. FFA treatment reduced both basal ROS production and muscle [Ca2+]i and [Na+]i in middle-aged and aged muscle fibers compared to fibers and muscles of untreated 12 and 24-months old mice. [Ca2+]i was reduced to 134 ± 8 nM in middle-aged muscle and to 246 ± 40 nM in muscle from aged mice. Likewise [Na+]i was reduced to 9 ± 0.7 mM in middle-aged muscles and to 13 ± 1 mM in muscle from aged mice. FFA treatment also reduced age associated increases in plasma interleukin 6 and tumor necrosis factor-alpha (TNF-α) concentrations which were elevated in 12 and 24-months old mice compared to young mice and decreased age-related muscle damage as indicated by a reduction in serum creatine kinase (CK) activity. Our data provides a direct demonstration that normal aging is associated with a significant elevation [Ca2+]i, [Na+]i, and intracellular ROS production in skeletal muscle fibers. Furthermore, the fact that FFA reduced the intracellular [Ca2+], [Na+], and ROS production as well as the elevated IL6, TNF-α, and CK levels, led us to suggest that its pharmacological effect may be related to its action both as a TRPC channel blocker and as an anti-inflammatory.